Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\sqrt{\left(3-\sqrt{5}\right)^2}+\sqrt{6-2\sqrt{5}}\)
\(=3-\sqrt{5}+\sqrt{\left(\sqrt{5}-1\right)^2}\)
\(=3-\sqrt{5}+\sqrt{5}-1=2\)
\(\sqrt{9+4\sqrt{5}}=\sqrt{\left(\sqrt{5}+2\right)^2}-\sqrt{5}\)
\(=\sqrt{5}+2-\sqrt{5}=2\)
Chúc học tốt!!!!!!!!!!!!!
\(=\sqrt{\left(\sqrt{3}+2\right)^2}-\sqrt{\left(2\sqrt{3}-1\right)^2}\)
\(=\sqrt{3}+2-2\sqrt{3}+1\)
\(=3-\sqrt{3}\)
\(\sqrt{242}.\sqrt{26}.\sqrt{130}.\sqrt{0,9}-\left(\sqrt{2}-1\right)\left(\sqrt{2}+1\right)\)
\(=\sqrt{121}.\sqrt{2}.\sqrt{2}.\sqrt{13}.\sqrt{13}.\sqrt{10}.\sqrt{0,9}-\left(2-1\right)\)
\(=11.2.13.\sqrt{9}-1=286.3-1=857\)
\(\frac{3-\sqrt{6}}{\sqrt{12}-\sqrt{8}}-\frac{\sqrt{15}-\sqrt{5}}{2\sqrt{12}-4}+\frac{\sqrt{17-4\sqrt{15}}}{4}\)
\(=\frac{\sqrt{3}\left(\sqrt{3}-\sqrt{2}\right)}{2\left(\sqrt{3}-\sqrt{2}\right)}-\frac{\sqrt{5}\left(\sqrt{3}-1\right)}{4\left(\sqrt{3}-1\right)}+\frac{\sqrt{\left(2\sqrt{3}-\sqrt{5}\right)^2}}{4}\)
\(=\frac{\sqrt{3}}{2}-\frac{\sqrt{5}}{4}+\frac{2\sqrt{3}-\sqrt{5}}{4}\)
\(=\sqrt{3}-\frac{\sqrt{5}}{4}\)
\(\sqrt{300}-\sqrt{27}+4\sqrt{3}\)
=\(10\sqrt{3}-3\sqrt{3}+4\sqrt{3}\)
=\(11\sqrt{3}\)
\(\sqrt{300}-\sqrt{27}+4\sqrt{3}\)
\(=\sqrt{10^2.3}-\sqrt{3^2.3}+4\sqrt{3}\)
\(=10\sqrt{3}-3\sqrt{3}+4\sqrt{3}\)
\(=11\sqrt{3}\)
\(\frac{2+2\sqrt{5}}{3-\sqrt{5}}=\frac{\left(2+2\sqrt{5}\right)\left(3+\sqrt{5}\right)}{\left(3-\sqrt{5}\right)\left(3+\sqrt{5}\right)}=\frac{6+2\sqrt{5}+6\sqrt{5}+10}{3^2-\sqrt{5}^2}=\frac{16+8\sqrt{5}}{4}=\frac{4\left(4+2\sqrt{5}\right)}{4}=4+2\sqrt{5}\)
= 0.8740320489
\(\frac{\sqrt{2}.\sqrt{3-\sqrt{5}}}{\sqrt{2}}=\frac{\sqrt{6-2\sqrt{5}}}{\sqrt{2}}=\frac{\sqrt{5-2\sqrt{5}.1+1}}{\sqrt{2}}=\frac{\sqrt{\left(\sqrt{5}-1\right)^2}}{\sqrt{2}}\)
\(=\frac{\sqrt{5}-1}{\sqrt{2}}=\frac{\sqrt{10}-\sqrt{2}}{2}\)